Effectiveness of episiotomy in preventing third and fourth degree perineal tear - Devkota, AR; Rana, A; Gurung, G; Amatya, A (Journal of Institute of Medicine Nepal, 2007)
Background: To verify effectiveness of episiotomy in preventing third and fourth degree perineal tear. Materials and Methods: Retrospective analysis of obstetric variables in 30 women who had sustained third and fourth degree perineal tear, compared with remaining 9632 vaginal deliveries during the same period. Obstetric department of Tribhuwan University Teaching Hospital, Institute of Medicine, Kathmandu, Nepal. This study identified 9662 vaginal deliveries over 42 months period from April 2003 to October 2006 from obstetric records. Thirty cases who sustained third and fourth degree perineal tear were further analyzed. Results: Overall rate of third and fourth degree perineal tear was 0.22% (n=21) and 0.09% (n=9), respectively. Episiotomy was given to 49.0% (n=4250) of the total vaginal delivery that occurred during that period. Among women who were given episiotomy 0.42% (n=18) had severe degree perineal tear. Among women who were not given episiotomy 0.22% (n=12) had severe degree perineal tear. Among cases who had severe degree perineal tear 76.7% (n=23) were primi, compared to 23.3% multipara. Women who had sustained third degree perineal tear had slightly smaller babies of average birth weight 3.22 kg compared to 3.31 kg in those who had fourth degree tear. Post dated delivery occurred in 46.7% (n=14) cases. 15.4% (n=4) cases were induced with prostaglandins and 46.2% (n=12) were augmented with syntocinon. Forceps was used in 3.33% (n=1) and vacuum was used in 10.0% (n=3) cases. Conclusion: Severe degree perineal tear occurred in almost double cases who were epitomized than those who were not. Large birth weight of baby, primiparity, postdated delivery and instrumentation were related to severe degree perineal tear. Key words: Episiotomy, perineal tear, vaginal deliveries The full text of this paper is available at Journal of Institute of Medicine website